1993
DOI: 10.1002/star.19930450205
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Water Content on the Compaction Behaviour of Potato Starch

Abstract: This study compares treatments of the compaction and stress transmission data obtained for potato starch at different water contents in the range 5‐25% (wet weight basis) compacted in a cylindrical geometry. An increase in water content leads to a greater density for a given pressure, approaching zero porosity at the higher water contents. The limiting gradient of the Heckel plot, which is the reciprocal of a generalised deformation stress, falls with increasing water content due to a plasticisation mechanism.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…Ollet et al [24] observed that in the region of the glass transition (at ambient temperatures with a water content of 20% the elastic modulus is extremely sensitive to water content. Above 20% they found that starch granules were rubbery and allowed extensive elastic deformation in response to the stress, whilst below 18% the elastic modulus was more typical of a glass and only relatively small elastic deformations could occur.…”
Section: Discussionmentioning
confidence: 99%
“…Ollet et al [24] observed that in the region of the glass transition (at ambient temperatures with a water content of 20% the elastic modulus is extremely sensitive to water content. Above 20% they found that starch granules were rubbery and allowed extensive elastic deformation in response to the stress, whilst below 18% the elastic modulus was more typical of a glass and only relatively small elastic deformations could occur.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] The mechanical properties of starch are well documented in the literature. [11][12][13][14] It has been reported that pregelatinised starch, which is produced by heating an aqueous slurry of starch, followed by a thermic dehydration process 4) (e.g.…”
mentioning
confidence: 99%
“…[11][12][13][14] The plasticity of starch was found to be dependent on particle size, size distribution, particle shape, moisture content and compaction speed. 8,15) Also, starch is extremely sensitive to the softening effects of alkaline stearate lubricants and thus, it has a high strain sensitivity index.…”
mentioning
confidence: 99%
“…In one study (Ollett ot ail., 1991), the Young's modulus of wheat starch was found to decrease from 1500 MPa to 50 MPa when the water content was increased from 16 to 20%. Although the starches were reported to exhibit limited yielding (Rees and Rue, 1978), electron microscopic investigation shows that this is relatively insensitive to water content for potato starch (Ollett et al, 1993b). The large variation in deformation stress determined from the Heckel plot is predominantly due to the changes in elastic modulus with water content.…”
Section: Resultsmentioning
confidence: 98%